Analysis of the Influence of Economic Digitalization, Entrepreneurial Knowledge and Social Media Skills on Student Entrepreneurship Interest - Fitria, Noka; Khusaini, Moh. (Sekolah Pascasarjana Universitas Brawijaya, 2023)
The study aims to determine student’s interest in entrepreneurship, especially FEB UB students, and the factor influecing it. This type of research is quantitative research using primary data obtained from online questionnaires via Google Form, wich will be disturbed to prospective respondents. This study uses multiple linear regression analysis. The population of this study was FEB UB students in the 2019-2022 class, with sample of 100 students. The result of this study indicates that economic digitalization has a positive and significant effect on student entrepreneurship interest, while entrepreneurial knowledge has a negative and insignificant impact on entrepreneurship interest, and social media skills have a positive but not significant effect on entrepreneurship interest. Keywords: economic digitalization, entrepreneurial knowledge, social media, entrepreneurship interest